“It Takes Two to Tango”: Role of Neglected Macrophage Manipulators Coronin 1 and Protein Kinase G in Mycobacterial Pathogenesis - Saha, Saradindu; Das, Payel; BoseDasgupta, Somdeb (Frontiers in Cellular and Infection Microbiology, 2020)
Macrophages being the connecting link between innate and adaptive immune system plays a crucial role in microbial antigen presentation and orchestrates the subsequent clearance of microorganisms. Microbial invasion of macrophages, trigger a plethora of signaling cascades, which interact among them to generate a dynamically altered hostile environment, that ultimately leads to disruption of microbial pathogenesis. Paradoxically, Mmycobacteria sp. um tuberculosis exploits several macrophage factors proteins such as Coronin 1, Calcineurin, LRG47, SOCS1, CISH, Gbp5 etc and secretes a number of virulence proteins factors such as PknG, PtpA, SapM, Eis etc to hijack some of these intra-macrophage, signaling cascades and thus thereby develops its own niche. Mycobacteria recruit and retain the macrophage cortical protein Coronin 1 on its phagosome to hinder its fusion with lysosome Coronin 1, being a cortical protein is transiently recruited to all Mmycobacteria containing phagosomes, but only pathogenic mycobacteria can retain it on the phagosome, to hinder its maturation. Additionally, mycobacterial infection linked secretion of virulence factor Protein Kinase G through its phosphorylation, manipulates several macrophage signaling pathways and thus promotes pathogenesis at various stages, form early infection to latency to granuloma formation. Here we discuss the present status of mycobacteria engaged Coronin 1-dependent signalling cascades and secreted PknG related sequence of events promoting mycobacterial pathogenesis. Current knowledge about these two proteins in context of macrophage signalling manipulation encompassing diverse mechanisms like calcium-calcineurin signalling, reduced proinflamtory cytokine secretion, cytoskeletal changes and adaptation in acidic environment, which ultimately converge towards mycobacterial survival inside the macrophages has been discussed.